Dietary Walnuts Protect Against Obesity-Driven Intestinal Stem Cell Decline and Tumorigenesis - Guan, Fangxia; Tabrizian, Tahmineh; Novaj, Ardijana; Nakanishi, Masako; Rosenberg, Daniel W.; Huffman, Derek M. (Frontiers in Nutrition, 2018)
Obesity can negatively impact intestinal homeostasis, and increase colon cancer risk and related mortality. Thus, given the alarmingly high rates of obesity in the US and globally, it is critical to identify practical strategies that can break the obesity-cancer link. Walnuts have been increasingly recognized to mitigate cancer risk, and contain many bioactive constituents with antioxidant and anti-inflammatory properties that could potentially counteract pathways thought to be initiators of obesity-related cancer. Therefore, the purpose of this study was to determine if walnuts could preserve intestinal homeostasis, and attenuate tumorigenesis and growth in the context of obesity and a high calorie diet. To this end, we studied effects of walnuts on these parameters under different dietary conditions in wildtype mice, two independent Apc models (Apc1638N/+ and Apc∆14), and in MC38 colon cancer cells in vivo, respectively. Walnuts did not alter the metabolic phenotype or intestinal morphology in normal mice fed either a low-fat diet (LFD), LFD with 6% walnuts (LFD+W), high-fat diet (HFD), or HFD with 7.6% walnuts (HFD+W). However, walnuts did lead to a significant reduction in circulating CCL5 and preserved intestinal stem cell (ISC) function under HFD-fed conditions. Furthermore, walnuts reduced tumor multiplicity in Apc1638N/+ male HFD+W animals, as compared to HFD controls (3.7±0.5 v 2.5±0.3; P=0.015), tended to reduce the number of adenocarcinomas (0.67±0.16 v 0.29±0.12; P=0.07), and preferentially limited tumor growth in Apc∆14 male mice (P=0.019) fed a high-calorie western-style diet. In summary, these data demonstrate that walnuts confer significant protection against intestinal tumorigenesis and growth and preserve ISC function in the context of a high-calorie diet and obesity. Thus, these data add to the accumulating evidence connecting walnuts as a potentially effective dietary strategy to break the obesity-colon cancer link.